Indonesian language teachers’ teaching performance and students’ learning outcomes - Basilius Redan Werang; I Made Suarjana; Kariyanti Kumala Dewi; Sandra Ingried Asaloei (International Journal of Evaluation and Research in Education (IJERE), 2023)
Teachers are an important component in modern society because they have a very extraordinary role in the lives of children, especially in the early years of their development. This study aimed to describe the teaching performance of Indonesian language teachers and how it affects the Indonesian language learning outcomes of state junior high school students of Merauke, Indonesia. To achieve this goal, the researchers used a quantitative approach with a survey research design. Data on the teaching performance of Indonesian language teachers were obtained by distributing a survey questionnaire to students who had been designated as respondents, while data on students’ learning outcomes were obtained by getting their academic transcripts. Obtained data were statistically analyzed using the software statistical package for the social sciences (SPSS) version 21. The results showed that the teaching performance of Indonesian language teachers has a significant positive effect on the learning outcomes of the state junior high school students of Merauke, Indonesia. The result indicated the importance of the school principals to focus their efforts to improve the teaching performance of Indonesian language teachers in order that students’ learning outcomes are adequately addressed.